The Role of Basic Education In Improving The Quality of Life of Fisherman Families In Ujungalang Village, Kampung Laut District, Cilacap - Putri, Raudya Setya Wismoko; Banowati, Eva; Utomo, Cahyo Budi; Hayati, Rahma; Septiani, Endah (Universitas Negeri Semarang, 2024)
This research aims to explore the role of basic education in improving the quality of life of fishing families in Ujungalang Village, Kampung Laut District, Cilacap. Basic education has an important role in equipping fishermen's children with basic knowledge and skills that can open up opportunities for a better life. The research method used is a qualitative study with a phenomenological approach, where data is collected through in-depth interviews, participant observation and document analysis. The research results show that basic education plays a significant role in improving the quality of life of fishing families through several aspects, namely increasing literacy and numeracy, character formation and work ethics, as well as economic empowerment through increasing skills and knowledge. Children who receive basic education tend to have higher aspirations to continue their education to a higher level, which in turn has a positive impact on the overall well-being of the family. This research also identifies the main challenges faced by fishing families in accessing basic education, such as economic limitations, lack of adequate educational facilities, and minimal awareness of the importance of education. To overcome these challenges, collaboration is needed between the government, educational institutions and the community to create a supportive environment for the basic education of fishermen's children.